If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(n + 7) = n + -1(4 + -1n) Reorder the terms: 4(7 + n) = n + -1(4 + -1n) (7 * 4 + n * 4) = n + -1(4 + -1n) (28 + 4n) = n + -1(4 + -1n) 28 + 4n = n + (4 * -1 + -1n * -1) 28 + 4n = n + (-4 + 1n) Reorder the terms: 28 + 4n = -4 + n + 1n Combine like terms: n + 1n = 2n 28 + 4n = -4 + 2n Solving 28 + 4n = -4 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 28 + 4n + -2n = -4 + 2n + -2n Combine like terms: 4n + -2n = 2n 28 + 2n = -4 + 2n + -2n Combine like terms: 2n + -2n = 0 28 + 2n = -4 + 0 28 + 2n = -4 Add '-28' to each side of the equation. 28 + -28 + 2n = -4 + -28 Combine like terms: 28 + -28 = 0 0 + 2n = -4 + -28 2n = -4 + -28 Combine like terms: -4 + -28 = -32 2n = -32 Divide each side by '2'. n = -16 Simplifying n = -16
| 3x+10=23-8x | | -17.5=3.5c | | 4(n+7)= | | y=2x^3+x^2-x | | 4(x-72)=-16 | | 3(x-5)+4(2x+3)=30 | | 6n+(7n)=42 | | 9x=12-3y | | 7n+3=2n+33 | | 3-5(2x-7)=5-(4-2x) | | 7(x+4)+5x=30 | | n+(-2)=-14 | | 4(Y-3)-6(y+1)=4(3y+4)-2(8-6y) | | r+(-3)=10 | | -12+10y=15y+3 | | 390=30*3+42h+195 | | x-(-6)=20 | | x-.1x=27.76 | | 9n+8=71 | | 96-28*x=-x^2 | | -3y+2= | | 5n-15=15 | | 96-28x=x^2 | | ln(x+1)=ln(3x+3) | | -2(4-3*0.7)= | | 4x^3+3x^2-2=0 | | p-0.1=1.4 | | -2(4-3y)=3+9(y-1) | | x=.8x+100 | | 2+5(x-2)=7 | | 4x+1.1-1.2x=0.3x-2.4 | | 7+b=-5 |